O projeto integrador (PI) como instrumento de efetivação do currículo integrado - Feitosa, Robson de Sousa (2019)
The research on “The integrative project (PI) as an instrument for implementing the integrated curriculum” aims to analyze whether the PIs contribute to the construction of the integrated curriculum in high school courses in an integrated way to professional training at IFPA, Campus Bragança, investigating specifically the integrated technical course of Events. Does this research intention when entering the Professional Master's Program in Professional and Technological Education part of the questions of how PIs arise? Are they an attempt to curricularize interdisciplinarity? And, mainly, how can PIs contribute to the construction of the integrated curriculum in high school courses in an integrated way with professional training at IFPA, Campus Bragança? This work is part of the macro project "Organization of the curriculum integrated in the EPT" of the research line of the program "Organization and management of pedagogical spaces in the EPT". The qualitative methodological approach used critical action research, with documental and bibliographic research techniques, interviews, participant observation and roaming diary, pedagogical workshops and content analysis. The results indicate that the IP emerges as an IFPA institutional policy for curriculum integration, that the integrated curriculum can be implemented through the IP, and that the educational product, which is the pedagogical workshop, was constituted as a space for dialogue and teaching. The conclusions indicate that the obligation to comply with IP as a curricular component may have a limitation due to compulsoriness, but at the same time it can be an instrument of implementation of the integrated curriculum. They also indicate that IP with planning, participatory management of teaching processes and horizontalization through dialogue leads to an emancipatory and self-forming perspective for all subjects involved, as it reflects the conceptual basis of Vocational and Technological Education